Pathway to the cerebral cortex for impulses from tendon organs in the cat's hind limb. - McIntyre, A K (1985)
In cats anaesthetized with alpha-chloralose, extracellular, recordings were made from neurones lying in nucleus Z. All cells could be excited by electrical stimulation of ipsilateral hind-limb muscle nerves at group I strength. Many cells showed an irregular background discharge. In response to graded contraction of hind-limb muscles, including lateral gastrocnemius, soleus and flexor digitorum longus, cell discharge changed in a manner suggesting that it was driven by input from muscle spindles or from tendon organs. Responses of individual nucleus Z cells were always specific to one kind of receptor and there was no evidence of convergence of afferent impulses from spindles and tendon organs. Nucleus Z neurones excited by muscle group I input could be antidromically driven by stimulation of the contralateral thalamus identifying them as bulbo-thalamic projection neurones. The same cells could be driven trans-synaptically by stimulation of the ipsilateral anterior lobe of the cerebellum. It was possible using a collision test to show that afferent fibres synapsing on nucleus Z cells were collaterals of dorsal spinocerebellar tract cells. It is concluded that nucleus Z is a brain stem relay for afferent information from muscle spindles and tendon organs which is destined for the cerebral cortex.